Assessing the employees efficiency and adaptive performance for sustainable human resource management practices and transactional leadership: HR-centric policies for post COVID-19 era - AlAbri I.; Siron R.B.; Alzamel S.; Al-Enezi H.; Cheok M.Y. (Frontiers Media S.A., 2023)
Efficiency; Natural resources management; Personnel training; Resource allocation; Surveys; Human resource management practices; Human resources management; Job enlargements; Organisational; Organizational efficiency; Performance; Performance appraisal; Post covid; Sustainable human resource; Transactional leadership; Human resource management